Shigella dysenteriae infection activates proinflammatory response through β-catenin/NF-κB signaling pathway. - Ashidha Gopal; Iyer Soumya Chidambaram; Niranjali Devaraj; Halagowder Devaraj (PLoS ONE, 2017)
Shigella dysenteriae (S.dysenteriae) the causative agent of bacillary dysentery invades the human colonic epithelium resulting in severe intestinal inflammatory response and epithelial destruction. However, the mechanism by which S.dysenteriae infection regulates proinflammatory cytokines during intestinal inflammation is still obscure. In this study, we evaluated whether the interaction of β-catenin and NF-κB regulates proinflammatory cytokines TNF-α and IL-8 by modulating GSK-3β activity during S.dysenteriae infection in rat ileal loop model. Here we demonstrated that S.dysenteriae infection stimulate β-catenin degradation which in turn decreased the association between NF-κB and β-catenin. Also, we showed that S.dysenteriae infection increased GSK-3β kinase activity which in turn phosphorylates β-catenin for its degradation by ubiquitination and upregulates IL-8 through NF-κB activation thereby leading to inflammation. Thus these findings revealed the role of β-catenin/ NF-κB and GSK-3β in modulating the inflammatory response during bacterial infection and also showed that β-catenin acts as a critical regulator of inflammation.